Overview: Research on hydroelastic responses of VLFS in complex environments. (July 2021) - Ding, Jun; Wu, Yousheng; Xie, Zhuoyu; Yang, Weinan; Wang, Siyu; Yu, Jun; Yu, Tao
Abstract: In the past several decades, extensive investigations have been carried out on the hydroelastic responses of Very Large Floating Structures (VLFS) in the deep open sea by researchers around the world. However, when tackling the hydroelastic problems of VLFS used as the protection and exploitation of marine resources near offshore and islands, the effects of complex environments, such as the seabed profile and inhomogeneous wave conditions should be taken into account. Based on the development history of VLFS and the process of classical hydroelasticity of VLFS, the research results of hydroelastic responses of VLFS in complex environments have been systematically summarized in this paper, so as to provide a basis for the further research. Highlights: Many factors have significant influences on the hydroelastic responses of VLFS deployed near seashore or an island. The research results of hydroelastic responses of VLFS in complex environments have been systematically summarized. The challenging key technical problems and the further development of the VLFS are also discussed.